Outlines of Contemporary South Slavic Interliterary Reception - Latković, Ivana (Slavistična prepletanja 6, 2025)
The paper presents the dominant tendencies of interliterary reception of South Slavic literatures after 1990, with special emphasis on the reception practice in the last five years. In a short introductory overview, two main trends in the study of South Slavic literatures in the 20th and 21st centuries are presented, namely with the aim of succinctly presenting their rich tradition, as well as delineating the dominant literary historical and literary critical insights today. The presentation of South Slavic interliterary reception is further presented in its two fundamental aspects, translation and literary criticism. This includes translations of prose, as today's most widely read literature, but only its book editions. Contemporary literary criticism is discussed in the transitional and post-transitional context, considering its changed status and role at this time, different modes of realization, as well as the type of today's reader. The research shows that with the second decade of the 21st century mutual translation of South Slavic literatures is gradually strengthening, and also that their interliterary reception is finding its way.